ESTUARINE AREAS IN HAI PHONG CITY - POSITION RESOURCES AND POTENTIAL FOR DEVELOPMENT - Thanh, Tran Duc; An, Le Duc; Trang, Trinh Minh (Vietnam Journal of Marine Science and Technology, 2014)
The estuarine areas (EAs) in Hai Phong have great potential for the soci-economic development of this city. Regarding the geo-natural resources, EAs are the focal location of the waterway systems; transition zone between mainland and sea; hinge between the Northeast coastal zones and Red River Delta; and the gateway to Northern Vietnam from South China. They are classic delta and estuary having, semi-closed structure, with stably large and deep river mouths, and extensive intertidal zones. EAs have the long lasting natural evolution and locate in the coastal tropical monsoon zone, where the natural conditions are rather stable and the natural disasters are not too harsh. This is also the region with other natural resource abundance; and especially the regimes of diurnal tide in large range typically bring huge benefits of economy and environment. With respect to the geo - economic resources, EAs are valuable sea wand gate in coastal Northern Vietnam and have the role in linking Hai Phong city with capital Ha Noi. These are the central area of the economic space in coastal zone of Northern Vietnam and are the centre of the economics system with two corridors (Hai Phong - Ha Noi - Nanning and Hai Phong - Ha Noi - Kunming)- one economic belt (Gulf of Tonkin) in the development process of international integration. In particular, they are favorable localities to prioritize development of marine economic sectors and key marine economic zone. Concerning the geo - politic resources, EAs are the development space of residential areas and coastal urbanization, the convergence of many factors that contribute to ensuring national security, support for national sovereignty and interests on the sea. This is also the place where the values of ​​unique indigenous culture are developed and preserved.